Does cognitive behavioral therapy using a self‐check sheet improve night‐time frequency in patients with nocturia? Results of a multicenter randomized controlled trial. (17th January 2021) - Kyoda, Yuki; Okada, Manabu; Kato, Ryuichi; Matsuki, Masahiro; Ito, Naoki; Takahashi, Atsushi; Tanuma, Yasushi; Tachiki, Hitoshi; Fukuta, Fumimasa; Hashimoto, Kohei; Kobayashi, Ko; Tanaka, Toshiaki; et al.
Abstract : Objective: To determine whether cognitive behavioral therapy using a self‐check sheet is effective in improving night‐time frequency of patients with nocturia. Methods: We carried out a multicenter, open‐labeled, randomized controlled trial in eight institutions. Patients having two or more episodes of nocturia were randomly assigned to either cognitive behavioral therapy with completion of frequency volume charts regularly (cognitive behavioral therapy group) or frequency volume charts regularly alone (frequency volume charts group). The cognitive behavioral therapy checklist was composed of eight items: wake up time/bedtime, mealtime, napping, alcohol/caffeine intake, water intake, salt intake, exercise and taking a bath. A physician explained cognitive behavioral therapy within 5 min using a brief manual. The patients in the cognitive behavioral therapy group filled out the self‐check sheet every day. The primary end‐point was the difference in night‐time frequency based on the International Prostate Symptom Score Q7 at 4 weeks. Results: Of the 100 first‐visit patients randomly allocated, 37 in the cognitive behavioral therapy group and 41 in the frequency volume charts group completed the protocol. No difference was observed in the mean ± standard deviation of night‐time frequency at 4 weeks between the cognitive behavioral therapy group (2.6 ± 1.0) and the frequency volume charts group (3.1 ± 1.2; P  = 0.056). However, when six patients with achievement of cognitive behavioral therapy of <50% were excluded from the analysis, night‐time frequency at 4 weeks was significantly lower in the cognitive behavioral therapy group (2.5 ± 1.0) than in the frequency volume charts group (3.1 ± 1.2; P  = 0.027). Conclusions: The efficacy of cognitive behavioral therapy using a self‐check sheet for nocturia remains to be shown. However, strictly practicing cognitive behavioral therapy might be beneficial to these patients.